"Why don't you teach a course about intelligence?". Issue 7 (10th November 2017) - Barrett, David M.
Abstract: This article notes that it was a student who suggested to me that I teach a course on intelligence. After some thought, I acted on his idea. Selecting books for the course was a significant task. One 'lesson learned' in doing so was that, while some books on intelligence can be great reading for those already knowledgeable on the basics, they can be too sophisticated for undergraduates who (like most Americans) are ignorant about U.S. intelligence agencies and their place in the larger government. Other books have been nearly perfect for such students. Since Villanova University is a few hours from Washington, D.C., students have rarely encountered anyone who actually works in intelligence. Therefore, bringing alumni of our school who do just that work back to campus helps the course seem less 'ivory tower' to students. As I am a historian, as much as a political scientist, I find that certain documents I have found in archives can be fascinating reading for students in the course.